Sonographic evaluation of maternal kidneys in normal pregnancy - Dawood, Shawnm Nasih; Amin, Salwa Ahmed; ShekhMuhammed, Samira Salim (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and Objectives: Renal disease can affect the outcome of pregnancy. The renal system undergoes significant physiological and anatomical changes during pregnancy. Ultrasound is the commonest imaging modality used in the evaluation of the abdominal organs in pregnancy. The purpose of this study was to sonographically evaluate the kidneys in normal pregnancy. Methods: A prospective descriptive study in which real time B-mode renal ultrasound was performed on 500 pregnant women attending for a routine obstetric ultrasound scan. Questions about the age, parity and presence of loin pain were asked. Obstetrical ultrasound examination was initially performed followed by examination of maternal kidneys. Results: Renal collecting system dilatation was the main abnormal finding; it was present in 18.2% of cases, (15.2% right side and 3% left side). Bilateral hydronephrosis was seen in (2.6%) of cases. Rate of hydronephrosis was more in primiparous women. Other findings were renal stones (2.8% right and 1.8% left sides, respectively), ureteric stone (0.2%) and acute pyelonephritis (1%). Conclusions: This study established the value of renal sonography in the pregnant women, though not a common condition. Renal collecting system dilatation was the main finding. A significant proportion of patients with asymptomatic renal calculi were detected incidentally.